EU drug markets report: strategic overview (Publications Office of the European Union, 2016)
This report explores the concept of the illicit drug market within the broader context of changing patterns of drug use, cultural and social factors and links to wider criminality. Drug markets continue to be one of the most profitable areas for organised crime groups (OCGs) and it is estimated that EU citizens spend over EUR 24 billion (range EUR 21 to 31 billion) every year on illicit drugs. The impacts that drug markets have on society are correspondingly large and go beyond the harms caused by drug use. They include involvement in other types of criminal activities and in terrorism; impacts on legal businesses and the wider economy; strain on and corruption of government institutions; and impacts on wider society. Three overarching themes emerge from our analysis: - The increasing organisational and technical complexity, interconnectedness and specialisation of groups involved in drug markets. - Globalisation and technology are accelerating the rate of change in the drug market. - Drug market-related activities are concentrated in a number of established and emerging geographical locations. These developments challenge those trying to respond to the problems created by the illicit drug market and the associated wider problems and suggest that: nn A systemic analysis of drug market business models will be helpful for both operational and policy purposes. - Partnerships between national authorities and with industry are becoming ever more important, as is engagement with international organisations and third countries. - Efficient use of resources can be achieved through the identification and targeting of geographical locations where drug market-related activities are concentrated. - Continuing recognition of the value of a strategic response, informed by sound information used to identify new opportunities as well as challenges, is essential.